Evaluation of the Markers of Inflammation in the Umbilical Cord Blood of Newborns of Mothers with Thrombophilia. (11th September 2014) - Wirstlein, Przemyslaw K.; Mikołajczyk, Mateusz; Jasiński, Piotr; Skrzypczak, Jana
<x xml:space="preserve">Abstract</x> Objective To answer the question as to whether the markers of thrombophilia in pregnant women, whose pregnancies ended in success, are reflected in the level of inflammation in the blood of the umbilical cord of the newborn. Materials and methods Umbilical cord blood and placenta after childbirth were secured from 16 patients with inherited (n = 7), acquired (n = 9) thrombophilia, and control group (n = 20). The concentrations of cytokines IL1β, IL10, TNFα, C5a anaphylatoxin, and granzyme A were assessed. decay accelerating factor (DAF) and membrane cofactor protein (MCP) levels were determined in the placentas, and the incidence of thrombotic changes was evaluated. Results Higher levels of anaphylatoxin C5a (P = 0.041), TNFα (P = 0.016), and IL1β (P = 0.037) were observed in the study group compared to the control group. In the study group, C5a levels correlated with the levels of TNFα (P = 0.018) and IL1β (P = 0.012). Higher levels of DAF and MCP proteins in study group were found in the control group (P < 0.001). In placentas from study group, there was a more frequent occurrence of incidences of thrombotic changes. Conclusion The observed, increased levels of pro‐inflammatory factors in the cord blood of newborns of mothers with thrombophilia may result from a reaction of the prothrombotic and pro‐inflammatory markers of thrombophilia present in maternal blood.